Algorithmic Trading in Forex Markets: The Impact of AI-Driven Strategies on Liquidity and Market Efficiency - Ganesh Marimuthu, (International Journal of Scientific Research in Computer Science, Engineering and Information Technology, 2025)
This comprehensive article examines the transformative impact of artificial intelligence and machine learning technologies on the foreign exchange market. The article explores how AI-driven systems have revolutionized trading strategies, order execution mechanisms, and liquidity provision in forex markets. The article encompasses the evolution of market microstructure, the emergence of non-bank liquidity providers, and the challenges posed by market fragmentation. The article explores the application of advanced technologies including deep neural networks, natural language processing, and reinforcement learning in forex trading, while also addressing the regulatory considerations and risk management protocols that have evolved alongside these technological advancements. Furthermore, the article evaluates the implications of these developments for market efficiency, price discovery, and systemic stability, providing insights into the future trajectory of forex markets as quantum computing and advanced AI integration continue to reshape the trading landscape.
Keywords: Algorithmic Trading; Artificial Intelligence; Financial Markets; Machine Learning; Risk Management